Penggunaan Media Konkret Bingo BAKU JAGA untuk Meningkatkan Kemampuan Membaca Kosa Kata Siswa Kelas 1 Sekolah Dasar - Jannah, Miftahul; Nasution, Ismail Saleh; Khairani, Khairani (Medan Resource Center, 2025)
This classroom action research investigates the effectiveness of Bingo BAKU JAGA, a culturally infused concrete learning medium, in enhancing vocabulary reading skills among first-grade students at SDN 060858 Medan Tembung. Designed as a game-based instructional tool, Bingo BAKU JAGA integrates local cultural elements to support the recognition and reading of syllables and words. The study was conducted in two cycles encompassing planning, implementation, observation, and reflection stages, involving a total of 21 students. The initial cycle revealed moderate improvement, while the second cycle demonstrated a significant increase in both student engagement and academic performance, with the proportion of students reaching the mastery level rising from 52% to 86%. These findings suggest that the integration of interactive, culturally contextualized media such as Bingo BAKU JAGA can substantially contribute to the development of foundational literacy skills in early primary education. The study concludes that using culturally relevant learning strategies fosters a more engaging and effective literacy learning environment for young learner.